Extracting nearshore wave properties from video: A new method for coastal estuaries. (5th November 2020) - Colvin, Jeffrey; Lazarus, Steven; Splitt, Michael
Abstract: Wave measurements, such as height and period, are important in understanding estuarine and coastal processes as well as air-sea interactions, which are important in the validation of hydrodynamic models and improvements in the parameterizations needed for atmospheric models. This paper presents and evaluates a relatively inexpensive and portable video-based method of measuring the nearshore wave properties of a coastal estuary. The proposed system uses a GoPro camera along with a set of scripts to perform camera calibration and remove lens distortions. Significant wave heights and peak frequencies are then extracted from the video without the need for the ground control points (objects of known physical location in relation to the camera) as used in previous studies. By not relying on ground control points, the system becomes portable and easy to deploy, allowing the collection of wave data from various locations on the estuary. The estimated significant wave heights and peak frequencies were validated with a sonic wave gauge located in the camera's field of view. Percent error and RMSE were calculated and indicate the proposed method is robust and the errors (estimated at less than 6%) are consistent with other video-based methods that use multiple cameras and ground control points. Highlights: A new method to extract wave properties from video is tested on a coastal estuary. Ground control points are not required for the proposed video-based method. Various lighting and wind conditions are tested and validated with a sonic wave gauge. Errors are consistent with previous studies that used ground control points.